First record of the Black Bullhead Ameiurus melas (Pisces, Ictaluridae) in the Republic of Macedonia - Ristovska, Milica; Arsovska, Julijana; Kostov, Vasil; Cvetkovska-Gjorgjievska, Aleksandra; Prelik, Dana; Radevska, Kristina (Macedonian Journal of Ecology and Environment, 2017)
The North American catfish – the black bullhead, Ameiurus melas (Rafinesque, 1820) is recorded for the first time in the Republic of Macedonia, in Pčinja River. Nine individuals of this ictalurid fish species were fished from the anglers in Pčinja River on September 2015 and another 8 samples on May 2016 were brought to the Institute of Biology, Faculty of Natural Science and Mathematics in Skopje. After a detailed observation of the external morphological features, osteology architecture, it was concluded that analysed individuals had all the distinguishing features of the species A. melas. The presence of different size class permitted the supposition that the black bullhead has established a selfsustaining population in this river.